Central Haemodynamics and Prediction of Cardiovascular Events in Patients With Erectile Dysfunction. (7th December 2016) - Vlachopoulos, Charalambos; Ioakeimidis, Nikolaos; Rokkas, Konstantinos; Angelis, Athanassios; Terentes-Printzios, Dimitrios; Kratiras, Zisis; Georgakopoulos, Christos; Tousoulis, Dimitrios
Abstract: BACKGROUND: We investigated whether central hemodynamics predict major adverse cardiovascular events (MACEs) in erectile dysfunction (ED) patients beyond traditional risk factors. METHODS: MACEs in relation to aortic pressures and augmentation index (AIx) were analyzed in 398 patients (mean age, 56 years) with ED but without established cardiovascular (CV) disease. RESULTS: During the mean follow-up period of 6.5 years, a total of 29 (6.5%) MACEs occurred. The adjusted relative risk of MACEs was 1.062 (95% confidence interval (CI), 1.016–1.116) for a 10-mm Hg increase of aortic systolic pressure, 1.119 (95% CI, 1.036–1.155) for a 10-mm Hg increase of aortic pulse pressure (PP), and 1.191 (95% CI, 1.056–1.372) for a 10% absolute increase of AIx. While aortic pressures and AIx did not significantly improve the C -statistic models, the calibration for all indices was satisfactory. Regarding reclassification, the integrated discrimination improvement index (IDI) indicated improvement in risk discrimination of the models that included AIx and aortic PP compared to the reference model in identifying MACEs (IDI = 0.0069; P = 0.024, and IDI = 0.0060; P = 0.036, respectively). The based on categories for 10-year coronary heart disease risk and adapted at 6.5 years overall net reclassification index showed marginal and indicative risk reclassification for AIx (15.7%, P = 0.12) and aortic PP (7.2%, P = 0.20) respectively. CONCLUSIONS: Our results show for the first time that higher central pressures and AIx are associated with increased risk for a MACE in ED patients without known CV disease. Considering the adverse prognostic role of central hemodynamics on outcomes, the present findings may explain part of the increased CV risk associated with ED.